Central Venoplasty in Patients with Cardiac Implantable Electronic Devices - Aljarie, Mohammed; Alahmari, Mohammed; Arabi, Mohammad (The Arab Journal of Interventional Radiology, 2021)
Objective The aim of this study was to assess the safety and effectiveness of the central venous angioplasty in patients with central venous occlusion and cardiac implantable electronic device (CIED) without lead extraction.Materials and Methods A retrospective study was used to evaluate the effectiveness of 37 central venous angioplasty procedure for 15 patients with CIED without lead extraction.Results Technical success was achieved in 97% (n = 36/37) and clinical success was achieved in 89% (33/37) of the procedures. One procedure failed recanalization of chronic total occlusion of the left subclavian vein, and the patient required fistula embolization due to severe arm swelling. Another procedure failed initially to recanalize long-segment occlusion involving the right subclavian vein/brachiocephalic vein and superior vena cava in a patient with a history of Hickman line and left-sided CIED. This was successfully recanalized and angioplastied on a subsequent session. No lead fracture or dislodgment was documented in any procedure. No procedure-related complication was documented within 2 weeks after the angioplasty. Six-month primary patency was achieved in 62% (23/37) of the procedures. Ten patients (66%) required an average of 1.4 reinterventions (range: 1–4 interventions) during the follow-up time with mean time to reintervention of 318 days (5–1,380 days). Two patients required early reinterventions within 10 days due to catheter dysfunction.Conclusion Findings of this study support the existing evidence on the safety and effectiveness of balloon angioplasty without lead extraction.
Keywords: balloon angioplasty; dialysis; Occlusion; pacemaker; stenosis